Effort Of Minke To Get His Right Reflected In This EarthOf Mankind By Pramoedya Ananta Toer (1975): An Individual Psychological Approach - Wijayanti, Hayu; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The major issue of this study is how effort of Minke to get his right reflected in This Earth of Mankind novel (1975). The objective of this study is to describe This Earth of Mankind novel based on structural elements of novel and to analyze effort of Minke to get his right reflected in This Earth of Mankind novel (1975) on the novel based on psychological approach. The researcher uses two data sources. The primary data source is This Earth of Mankind (1975) novel of Pramoedya Ananta Toer published by Lentera Dipantara. The secondary data is taken from other sources which are related to the primary data such as books, website, journal that related with This Earth of Mankind. The results of the study is the structural element of This Earth of Mankind novel shows the effort of Minke to get his right that he must fight in his life. First, the problem comes from his family, related with his parents that wants Minke become a Bupati like his father. The second, he must solve his problem after he turn out from HBS. Minke studied hard until he was accepted back as student in HBS and get graduating first in Surabaya. The third, after Minke married with Annelies, the problem came from the Amsterdam District Court that the guardianship of Annelies Mellema and her future upbringing in the Netherlands. Minke tried to fight the court, everything he tried. And the end he must accepted if Annelies must go to Netherlands. Although, Minke still trying following Annelies to Netherlands.